Pengaruh Kompetensi Nazhir Terhadap Efektivitas Wakaf Produktif dengan Akuntabilitas Keuangan Internal Sebagai Variabel Mediasi - Windi Indriani; Retno Dyah Pekerti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of nazhir competence on the effectiveness of productive waqf with internal financial accountability as a mediating variable in Tasikmalaya Regency. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 117 respondents consisting of waqf nazhirs in Tasikmalaya Regency. The data analysis techniques used were path analysis and the Sobel test to examine the mediating effect. The results showed that nazhir competence had a significant effect on internal financial accountability but did not have a significant effect on the effectiveness of productive waqf. Meanwhile, internal financial accountability had a significant effect on the effectiveness of productive waqf and was able to mediate the relationship between nazhir competence and the effectiveness of productive waqf. This study is expected to contribute to waqf institutions in improving the effectiveness of productive waqf through strengthening internal financial accountability and enhancing nazhir competence.